ANALISIS PENANGANAN KREDIT BERMASALAH PADA PT. PEGADAIAN (PERSERO) PEKANBARU KOTA - Rafika Eris; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to identify and analyze non-performing loans at PT. Pegadaian (Persero) Pekanbaru Kota, 2018-2021 . This study uses secondary data in the form of data of data obtained by the author manual reports and financial reports obtained from PT. Pegadaian (Persero) Pekanbaru Kota, which is needed by researchers for the analysis of non-performing loans. This research use descriptive qualitative approach. Data collection is obtained from interviews with PT. Pegadaian (Persero) Pekanbaru Kota and debtors. Checking the validity of the findings using source triagulation so that it is easy to analyze various problems that occcur in the company. The conclusions of this study are (1) factors from debtors and internal factors that because non-performing loans at PT. Pegadaian (Persero) Pekanbaru Kota (2) the handling of problems loans that have been implemented is routine collection, credit restructuring. Keywords: Non-Performing Loans, Handling Of Problem Loans.